1972
DOI: 10.1063/1.1677980
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Modulated Molecular Beams with Pyrolytic Graphite. I. Oxidation of the Basal Plane

Abstract: Reaction of molecular oxygen as a modulated molecular beam with the basal plane of pyrolytic graphite is investigated. The graphite surface participates in the reaction in an unusual fashion. Oxidation tends to create a highly reactive surface while thermal annealing tends to deactivate the surface. The imbalance of these two competing processes results in slow changes in surface reactivity during the course of an experiment, which is manifest as hysteresis in the rate of CO production. The surface chemical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
48
0
2

Year Published

1976
1976
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(61 citation statements)
references
References 19 publications
11
48
0
2
Order By: Relevance
“…The CO hysteresis behaviour observed by Olander et al [50] was again seen in more recent molecular beam experiments by Murray et al [51], as shown by the top right plot in Figure 2.5. They also observed that CO 2 production quickly slows with increasing surface temperature, which was attributed to the "Boudouard reaction" (CO 2 + (s) + C(b) − −− → (s) + 2 CO).…”
Section: Oxidationsupporting
confidence: 58%
See 1 more Smart Citation
“…The CO hysteresis behaviour observed by Olander et al [50] was again seen in more recent molecular beam experiments by Murray et al [51], as shown by the top right plot in Figure 2.5. They also observed that CO 2 production quickly slows with increasing surface temperature, which was attributed to the "Boudouard reaction" (CO 2 + (s) + C(b) − −− → (s) + 2 CO).…”
Section: Oxidationsupporting
confidence: 58%
“…The concept of there being two types of reaction zones was further investigated in molecular beam experiments by Olander et al [50]. Here, hysteresis behaviour was observed for CO production, whereby the apparent reaction probability was higher while heating up than when cooling down for the same surface temperature (shown in Figure 2.4).…”
Section: Oxidationmentioning
confidence: 90%
“…If we use a risky assumption that the oxidation of FeS(c) by 0 2 is similar to that Of Cgraphite, we can use a pre-exponential factor of -1012 and an activation energy for desorption of -85 kJ/mol (because 0 2 is likely not strongly bonded to FeS(c)); this leads to a desorption rate of -107 molecules/s. However this is conjectural, particularly since there is likely to be more than one temperature regime for reaction, as in the case of graphite oxidation (Olander et al, 1972). A further complication is the rate of difision of FeS(c) to the surface of the meteoroid; this is likely to be the rate-limiting step, but it is also likely to be the source of the persistent emissions.…”
Section: Heterogeneous Atmospheric Reactionsmentioning
confidence: 99%
“…For example, reactions (3) and (4) which are very exothermic, may be likened to the oxidation reaction ofgraphite (-99% vis 0 2 + Cgraphite + Cog, + 0 and -1% via 0 2 + Cgraphite + C02 gas) which has been studied by many authors (Olander et al, 1972;Rosner and Allendorf, 1968). In these studies it has been found that the catalytic reaction on graphite proceeds via a complex sequence of steps: ( I ) the surface has two different active sites; 0 2 chemisorbs preferentially on one site (labeled A) where it forms adsorbed CO and 0, where 0 is a labile adsorbed species.…”
Section: Heterogeneous Atmospheric Reactionsmentioning
confidence: 99%
“…For lesser energy ratios only Equations (64a) and (65a) need be considered and the resulting P 11 ~ P 11 ( 2).…”
mentioning
confidence: 99%